2018
DOI: 10.3389/fnhum.2017.00642
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Therapy Increases Go Timeouts in the Go/No-Go Task in Patients with Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is characterized by resting tremor, rigidity and bradykinesia. Dopaminergic medications such as L-dopa treat these motor symptoms, but can have complex effects on cognition. Impulse control is an essential cognitive function. Impulsivity is multifaceted in nature. Motor impulsivity involves the inability to withhold pre-potent, automatic, erroneous responses. In contrast, cognitive impulsivity refers to improper risk-reward assessment guiding behavior. Informed by our previous research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 113 publications
0
10
1
Order By: Relevance
“…Although previous studies sing Go no‐Go task paradigm have demonstrated that patients with PD are slower and make more errors than controls (Buccino et al, 2018; Yang et al, 2018), in our study all RT tasks were performed very efficiently. Differences between groups in accuracy where not significant except for the CRT‐S task, this finding cannot be interpreted accurately as the total dopamine dosing is not standard in all the included PD subjects.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Although previous studies sing Go no‐Go task paradigm have demonstrated that patients with PD are slower and make more errors than controls (Buccino et al, 2018; Yang et al, 2018), in our study all RT tasks were performed very efficiently. Differences between groups in accuracy where not significant except for the CRT‐S task, this finding cannot be interpreted accurately as the total dopamine dosing is not standard in all the included PD subjects.…”
Section: Discussioncontrasting
confidence: 57%
“…Simple Reaction Time‐Sustained Attention to Response Task (SRT‐SART): This task allowed to measure response strategy‐inhibition. Similar tasks have been used previously in PD (Yang et al, 2018). Following the model of Robertson et al (Robertson et al, 1997), participants had to press the left mouse button when the stimulus (digits 1–9) appeared in the center of the screen and inhibited the response when it appeared as the number "3."…”
Section: Methodsmentioning
confidence: 99%
“…This study describes the pharmacological effect of dopamine agonist (DAA) therapy on frontal cerebral blood flow (CBF) in patients with PD, and the relationship between frontal cortical regional CBF (rCBF) and individual differences in inhibitory action control. DAA therapy improves motor symptoms in PD, and can alter the proficiency of inhibiting action impulses (Wylie et al, 2012;Claassen et al, 2015;Yang et al, 2016Yang et al, , 2018. Using noninvasive arterial spin labeling (ASL) MRI (Claassen et al, 2017), we examined a cohort of PD patients in the off-and on-DAA medication states to assess the effect of DAA on rCBF in frontal regions involved in motor inhibition, and the relationship between rCBF and action control performance as measured by a well-established cognitive test, the Simon task (Simon, 1969).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, functions such as memory encoding , association learning , reward processing (Cools, 2006;Macdonald and Monchi, 2011;Vo et al, 2014) are intact at baseline in PD relative to healthy older controls. These cognitive functions are actually worsened by dopaminergic therapy in PD (Cools, 2006;Gotham et al, 1984;Hiebert et al, 2019;Kish et al, 1988;Swainson et al, 2000;Yang et al, 2018), as well as in healthy elderly and young controls (Fungwe et al, 1992;Olefins et al, 1986;Vo et al, 2016).The dopamine overdose hypothesis is a prevaling explanation for this effect of dopaminergic therapy in PD. In contrast to the degeneration of the SNc, dopamine-producing neurons in the ventral tegmental area (VTA) are relatively spared in PD (Kish et al, 1988).…”
Section: Introductionmentioning
confidence: 99%